2003
DOI: 10.1183/09031936.03.00065102
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of18fluorodeoxyglucose in the cystic fibrosis lung: a measure of lung inflammation?

Abstract: Positron emission tomography is a three-dimensional imaging technique that measures physiological effects, including metabolism. 18 Fluorodeoxyglucose has been extensively used as a tracer of cellular energy metabolism in the brain and in tumour detection. As neutrophils utilise glucose as an energy source during their respiratory burst, it was hypothesised that 18 fluorodeoxyglucose uptake, by these cells, could be interpreted as a measure of neutrophil activation in cystic fibrosis (CF).Ten adult CF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Regardless of which method is used, our data show significant differences between the rate of [ (39). However, in a reanalysis of their data, they found that the three patients who had an elevated uptake of [ 18 F]FDG by PET also had an increased rate of decline in pulmonary function (using the same criteria of Rosenbluth and colleagues [12])-consistent with our "rapidly declining" group-whereas the rate of decline in the seven patients who had no elevation in the uptake of [ 18 F]FDG was consistent with our "stable" group (Dr. R. Labiris, personal communication).…”
Section: Discussionmentioning
confidence: 68%
“…Regardless of which method is used, our data show significant differences between the rate of [ (39). However, in a reanalysis of their data, they found that the three patients who had an elevated uptake of [ 18 F]FDG by PET also had an increased rate of decline in pulmonary function (using the same criteria of Rosenbluth and colleagues [12])-consistent with our "rapidly declining" group-whereas the rate of decline in the seven patients who had no elevation in the uptake of [ 18 F]FDG was consistent with our "stable" group (Dr. R. Labiris, personal communication).…”
Section: Discussionmentioning
confidence: 68%
“…Thus, the optimal therapy for CF should be able to counteract the deleterious effects of neutrophil activation without impairing host defences against infection. CHEN and SCHUSTER [75] showed significant differences between the rate of FDG uptake by the lungs of 20 adult patients with CF versus seven adult normal volunteers and, similarly to LABIRIS et al [76], suggested that FDG-PET may discriminate patients with more rapidly declining lung function. In particular, they found that patients with CF and higher rates of decline in pulmonary function have higher numbers of neutrophils in BAL and higher PET-measured rates of FDG uptake.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Inflammation characterizes several lung diseases, including pneumonia, cystic fibrosis, chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome (ARDS), asthma, and interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF), among others (7,8,10,11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Because ARDS, COPD, and IPF can cause significant variability in the amounts of air, blood, and water in the lungs (Fig.…”
Section: Clinical Applications Investigated With 18 F-fdg Pet Imagingmentioning
confidence: 99%